STRATEGI KOMUNIKASI PEMASARAN ONLINE PRODUK BUSANA MUSLIM ZOYA MELALUI INSTAGRAM @ZOYALOVERS (Studi Deskriptif Kualitatif Akun Instagram @zoyalovers) - Giantika, Gan Gan (Jurnal Komunikasi, 2020)
Abstract  -  The use of online media being a medium which keeps growing functions , in addition to the media information and communication but also used as a media marketing , one services are from the internet through the instagram social networking .Instagram is social media which has the power of visual Through instagram shafco company enterprise use it as strategy of marketing communications to increase the sale of products through instagram @ zoyalovers account .This research to know the communications strategy online marketing products account muslim fashion through instgram @ zoyalovers Methods used by researchers in this research is the method. qualitative descriptive studyThis research in the use of this marketing strategy of marketing communications, communication with the approach planning content message to instagramnya account among others instagram @ zoyalovers with teaser, through, community approach working with influencers for the production of content and kurasi. productsThe result of this research produce that using social media instagram @ zoyalovers, zoya can increase online marketing communications products zoya muslim fashionKeywords: , Startegy,  marketing communications, instagram